Analysis of Customer Complaints Management in The Customer Care Department at PT X - Sarah Fathia Azzahra; Osly Usman; Suherdi (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Complaints are feedback resulting from dissatisfaction with a company's services or products. Besides indicating attention to the product or service, complaints also provide valuable information to improve the quality of customer service. For service companies, delivering quality service is key to success. It is crucial to have a dedicated department to handle complaints if the service provided is unsatisfactory. PT X is a large company in Indonesia that operates in the field of automotive auction services. In its operations, PT X frequently receives customer complaints and requires effective complaint management to address these grievances efficiently. This research aims to understand the implementation of customer complaint management in the Customer Care Department at PT X. This is a qualitative research study using a case study approach. Data collection was conducted through observation, interviews, and documentation. The sample for this study consists of 4 participants from the Customer Care Department at PT X. The results of the research show that PT X has implemented comprehensive customer complaint management through its Customer Care Department. This process includes stages from receiving, recording, processing, responding to, and resolving complaints, supported by clear SOPs, SLAs, and cost/claim matrices. Despite its success, PT X faces challenges in handling diverse customer characteristics, especially emotional or difficult-to-reconnect customers. The Customer Care team addresses these challenges by listening empathetically to complaints, providing clear information, and emphasizing training to enhance communication skills, emotional management, and conflict resolution.